Pengembangan Asesmen Formatif Terintegrasi Karakter Nilai Islam Berbasis Wordwall - Sari, Dewi; agustina, lady (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
This study aims to develop a formative assessment based on the Wordwall website, integrated with Islamic character values, as an interactive learning medium. The assessment not only measures students' cognitive understanding but also instills values of honesty, responsibility, and discipline. The researcher employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The resulting interactive assessment was implemented with 32 tenth-grade students of Class X F at SMA Muhammadiyah 3 Jember and validated by experts. The validation results indicated a